Fears and beliefs about running in adults with chronic low back pain: a mixed methods study from the ASTEROID randomised controlled trial - Christopher Neason; Claire L. Samanna; Scott D. Tagliaferri; Daniel L. Belavý; Paul Buntine; Matthew J. Clarkson; Clint T. Miller; Ulrike H. Mitchell; Niamh L. Mundell; David Scott; Patrick J. Owen (Sports Medicine - Open)
Abstract Background The stigma that running is unsafe for people with chronic low back pain (LBP) persists, despite recent studies showing that running training is feasible and beneficial in chronic LBP. We examined the beliefs about running in adults with chronic LBP. Methods Forty adults (20 female, mean [SD] age 33 [6] years) with non-specific chronic LBP were randomised to a 12 week digitally-delivered run-walk interval training intervention or waitlist control (ACTRN12622001276741). Participants completed the activity specific beliefs questionnaire (4-point Likert scale) and recorded pain intensity at baseline and 12 weeks. Running intervention participants (n = 19) completed semi-structured qualitative interviews at 12 weeks. Results Prior to randomisation, 10 participants (25%; intervention: n = 6) reported that running was unsafe. At follow-up, greater mean improvements were seen in the intervention group in the belief that running is safe. Specifically, belief in the safety of running on gravel (β [95%CI] 0.52[0.20, 0.84] points, P = 0.001), pavement (β [95%CI] 0.54[0.18, 0.89] points, P = 0.003), treadmill (β [95%CI] 0.49[0.14, 0.84] points, P = 0.006), and sprinting (β [95%CI]: 0.56[0.06, 1.06] points, P = 0.029) improved more than in the control group. Reflexive thematic analysis identified four themes: (a) fear and concerns that running may increase pain or lead to an injury, (b) negative beliefs are influenced by healthcare professionals and past experience, (c) fears can be overcome and be replaced with new beliefs, and (d) positive experience drives change in beliefs. Conclusions Completing a 12 week run-walk interval training intervention led to more positive beliefs about running in adults with chronic LBP. The identified themes can assist clinicians in addressing barriers and facilitators to implementing running interventions for chronic LBP. Trial registration: Australian New Zealand Clinical Trials Registry: ACTRN12622001276741. Registered on 29 September 2022.